Melamine resin coordinated cobalt@piperazine pyrophosphate microcapsule: an innovative strategy for imparting long-lasting fire safety to rigid polyurethane foams - Liu, Mengru (2024)
The persistent challenge of maintaining fire safety in flame retardant modified rigid polyurethane foams (RPUF) under humid conditions continues to be a concern. To address this challenge, a microcapsule named MF-Co@PAPP has synthesized, composed of melamine resin (MF, shell) and piperazine pyrophosphate (PAPP, core). This microcapsule was developed to enhance the long-lasting flame retardancy and smoke suppression of RPUF. These composites demonstrated a significant reduction in total heat release and total smoke release compared to pure samples, with decreases of 44% and 29%, respectively. The MF-Co@PAPP facilitated the carbonization process of RPUF, leading to the formation of a more stable char layer. The RPUF/MF-Co@PAPP composites exhibited the highest limiting oxygen index values, even after a 14-day immersion in water. This study introduces a target-driven design approach to enhance the fire safety of RPUF, offering inspiration for future development of tailored flame retardants.